Analysis of Transformational Leadership, HPWS, and Per-ceived Organizational Support on Employee Engagement - Armi Santia Dewi Ikhsan; Sandra Dewi; Supriyantoro Supriyantoro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Employee engagement is a critical factor in enhancing organizational performance, including in public sector organizations such as state-owned enterprises (BUMN). Low leadership inspiration, suboptimal work systems, and insufficient organizational support can reduce employee engagement levels. This study aims to analyze the influence of transformational leadership, high performance work system (HPWS), and perceived organizational support (POS) on employee engagement. A quantitative research method with a survey design was employed. Data were collected through valid and reliable questionnaires from the entire employee population, using proportional random sampling, resulting in a sample of 100 respondents. Multiple regression analysis was conducted to examine the relationships. The results indicate that transformational leadership, HPWS, and POS have a positive and significant effect on employee engagement. These findings underscore the importance of strengthening transformational leadership, implementing high-performance work systems, and providing consistent organizational support to enhance employee engagement. Managerial recommendations include improving leadership quality, competency-based workforce planning, and developing reward systems along with a collaborative and appreciative work culture.